Expression of the CGRP Family of Neuropeptides and their Receptors in the Trigeminal Ganglion - Edvinsson, Lars; Grell, Anne-Sofie; Warfvinge, Karin (Journal of molecular neuroscience, 2020)
The calcitonin gene-related peptide (CGRP) family of neuropeptides, consists of CGRP, adrenomedullin, amylin, and calcitonin. The receptors consist of either calcitonin receptor-like receptor (CLR) or calcitonin receptor (CTR) which for function needs an accessory protein, receptor activity-modifying proteins (RAMPs). CGRP has a pivotal role in primary headaches but the role of the other members of the CGRP family of peptides in headaches is not known. Here, we describe the expression of these molecules in the trigeminal ganglion (TG) to understand more on their possible role(s). Single or double immunohistochemistry were applied on frozen sections of rat TG using primary antibodies against CGRP, procalcitonin, calcitonin, adrenomedullin, amylin, RAMP1/2/3, CLR, and CTR. In addition, mRNA expression was measured by quantitative qPCR on TGs. CGRP and calcitonin showed rich expression in the cytoplasm of small to medium-sized neurons, and co-localized sometimes. Procalcitonin was observed in the glial cells. Immunoreactive fibers storing both CGRP and calcitonin were also observed. Adrenomedullin immunoreactivity was found in the satellite glial cells and in fibers, probably the myelinating Schwann cells. Amylin was found in the cytoplasm in many TG neurons. Levels of mRNA expression for adrenomedullin, amylin, CLR, RAMP1, RAMP2, RAMP3, and CTR were measured using qPCR. The experiments verified the expression of mRNA in the TG with the exception of CTR, which was above the limit of detection indicating little or no mRNA expression. In addition to the well-known CGRP receptor (CLR/RAMP1) and the receptor for calcitonin—CTR, we propose that other receptors exist in the rat TG: adrenomedullin receptor AM 2 (CLR/RAMP3) in mainly the satellite glial cells, amylin receptors AMY 1 (CTR/RAMP1) in mainly neurons, and AMY 3 (CTR/RAMP3) in the satellite glial cells. It is important to compare peptides and receptors side-by-side in studies to help address questions of actions resulting from cross-reactivity between receptors. Several of the diverse biological actions of the CGRP family of peptides are clinically relevant. Our findings demonstrate the specific ligand and receptor sites in the rat trigeminal ganglion, highlighting recognition mechanisms to facilitate drug development.